Osmotic Myelinolysis – a clinical case report - Ponte, Alcina (2003)
The authors describe a case of central pontine and extrapontine Myelinolysis in a man withalcoholism who presented to hospital with hiponatraemia. Central pontine Myelinolysis is ademyelination disorder and clinical manifestations include a rapidly evolving flaccid quadriplegia with inability to speak and swallow.This disorder has been seen in association withchronic alcoholism and electrolyte derangements. The degree of hyponatraemia or its rapid correction, may lead to this brain lesion.